ProBNP That Is Not Glycosylated at Threonine 71 Is Decreased with Obesity in Patients with Heart Failure. (1st September 2019) - Lewis, Lynley K; Raudsepp, Sara D; Prickett, Timothy C R; Yandle, Timothy G; Doughty, Robert N; Frampton, Christopher M; Pemberton, Christopher J; Richards, A Mark
Abstract: BACKGROUND: Heart failure (HF) is a leading cause of morbidity and mortality worldwide. Plasma concentrations of B-type natriuretic peptide (BNP) or its amino terminal congener (NT-proBNP) are used for HF diagnosis and risk stratification. Because BNP concentrations are inexplicably lowered in obese patients, we investigated the relationship between proBNP glycosylation, plasma NT-proBNP, and body mass index (BMI) in HF patients. METHODS: Three assays were developed to distinguish between total proBNP (glycosylated plus nonglycosylated proBNP), proBNP not glycosylated at threonine 71 (NG-T71), and proBNP not glycosylated in the central region (NG-C). Intraassay and interassay CVs were <15%; limits of detection were <21 ng/L; and samples diluted in parallel. RESULT: Applying these assays and an NT-proBNP assay to plasma samples from 106 healthy volunteers and 238 HF patients determined that concentrations [median (interquartile range)] of proBNP, NG-T71, and NT-proBNP were greater in HF patients compared with controls [300 (44–664), 114 (18–254), and 179 (880–3459) ng/L vs 36 (18–229), 36 (18–175), and 40 (17–68) ng/L, respectively; all P < 0.012]. NG-C was undetectable in most samples. ProBNP concentrations in HF patients with BMI more or less than 30 kg/m 2 were not different ( P = 0.85), whereas HF patients with BMI >30 kg/m 2 had lower NT-proBNP and NG-T71 concentrations ( P < 0.003) and higher proBNP/NT-proBNP and proBNP/NG-T71 ratios ( P = 0.001 and P = 0.02, respectively) than those with BMI <30 kg/m 2 . CONCLUSIONS: Increased BMI is associated with decreased concentrations of proBNP not glycosylated at T71. Decreased proBNP substrate amenable to processing could partially explain the lower NT-proBNP and BNP concentrations observed in obese individuals, including those presenting with HF.